10 Gbit s−1 Free Space Data Transmission at 9 µm Wavelength With Unipolar Quantum Optoelectronics. Issue 2 (22nd December 2021) - Dely, Hamza; Bonazzi, Thomas; Spitz, Olivier; Rodriguez, Etienne; Gacemi, Djamal; Todorov, Yanko; Pantzas, Konstantinos; Beaudoin, Grégoire; Sagnes, Isabelle; Li, Lianhe; Davies, Alexander Giles; Linfield, Edmund H.; et al.
Abstract: Free space optics data transmission with bitrate in excess of 10 Gbit s −1 is demonstrated at 9 µm wavelength by using a unipolar quantum optoelectronic system at room temperature, composed of a quantum cascade laser, a modulator, and a quantum cascade detector. The large frequency bandwidth of the system is set by the detector and the modulator that are both high frequency devices, while the laser emits in continuous wave. The amplitude modulator relies on the Stark shift of an absorbing optical transition in and out of the laser frequency. This device is designed to avoid charge displacement, and therefore it is characterized by an intrinsically large bandwidth and very low electrical power consumption. This demonstration of high‐bitrate data transmission sets unipolar quantum devices as the most performing platform for the development of optoelectronic systems operating at very high frequency in the mid‐infrared for several applications, such as digital communications and high‐resolution spectroscopy. Abstract : The realization of high‐frequency unipolar quantum optoelectronic devices enables the demonstration of high bitrate free space data transmission in the second atmospheric window. Data‐bits are written onto the laser emission using a large bandwidth amplitude modulator that operates by shifting the absorption of an optical transition in and out of the laser frequency.